New and interesting Meliolaceae members from Kerala - T.K. ABRAHAM, V.B. HOSAGOUDAR and (Indian Phytopathology, 2002)
Four members of the Meliolaceae found during a survey of foliicolous fungi in the Peppara and Neyyar wildlife sanctuaries in Thiruvananthapuram district of Kerala state in India are described and illustrated. The species include Asteridiella callista found on leaves of Stachytarpheta jamaicaensis, Meliola ardigoosii sp. nov. found on leaves of Buchanania lanzan, Meliola dendropthiicola sp. nov. found on leaves of Dendropthoe fulcata and Meliola pandanacearum sp. nov. found on leaves of a Pandanus sp.